Cytotoxicity and Mode of Cell Death of Dimethylarsinothionic acid (DMAS) in MDCK Canine Cocker Spaniel kidney Cells - Elmustafa, M; Wallace, H (Gezira Journal of Health Sciences; Vol 16 No 1 (2020), 2020)
Background: Exposure to arsenical compounds from natural or industrial sources is a global health problem which is associated with renal damage resulting from exposure to the parent arsenical or its metabolites. The metabolism of arsenicals plays a main role in their toxicity and previous studies have shown trivalent metabolites to be many folds more toxic than their pentavalent counterparts. Objectives: To investigate the toxicity and mode of cell death produced by the newly identified pentavalent metabolite, dimethylarsinothionic acid DMAS. Methods :  The toxicity and mode of cell death induced by DMAS was compared with other arsenicals in canine cocker kidney MDCK cells using the MTT (3(4,5-dimethylthiazole-2-yl)-2-5- diphenyl tetrazolium bromide) cytotoxicity and DAPI (4'-6-diamidino-2-phenylindole) assays respectively. Results:   DMAS produced toxicity levels (IC50 35 µM) at both 24 and 48 hours which was much higher than those of pentavalent, but lower, yet comparable, to those of trivalent arsenicals. The toxicity of DMAS was reduced in a dose dependant manner in the presence of the reactive oxygen scavenger dimethylsulphoxide DMSO suggesting a role of reactive oxygen species or oxidative stress in its toxicity. The levels of apoptosis induced by DMAS in the MDCK cells were much higher than those induced by the other arsenical compounds which suggest the possible involvement of a different or more profound mechanism in its toxicity. Conclusion : These results question the concept of valence dependant toxicity and suggest that other factors may influence arsenical induced toxicity such as functional groups or substitution of the arsenical compound in question.